2022
DOI: 10.3389/fnhum.2022.925283
|View full text |Cite
|
Sign up to set email alerts
|

Programming of subthalamic nucleus deep brain stimulation for Parkinson’s disease with sweet spot-guided parameter suggestions

Abstract: Deep Brain Stimulation (DBS) is an effective treatment for advanced Parkinson’s disease. However, identifying stimulation parameters, such as contact and current amplitudes, is time-consuming based on trial and error. Directional leads add more stimulation options and render this process more challenging with a higher workload for neurologists and more discomfort for patients. In this study, a sweet spot-guided algorithm was developed that automatically suggested stimulation parameters. These suggestions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Correspondingly, we found that even though the dorsal border of the STN limited our VISUAL-A approach based on individual T2-contrast in subject space, the core region of the n-map in MNI space widely surpassed the dorsal border of the atlas STN with about 30% located in the extranuclear compartment. Previous studies comparing the results of monopolar reviews and visual contact selection already reported higher levels of agreement for a visual approach compared to automatic sweet spot targeting, which might implicate a corrective impact of human interpretation during visual assessment [46,47]. We conclude that further development beyond the applied methodology is necessary to translate insights from probabilistic sweet spots to the individual patient.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Correspondingly, we found that even though the dorsal border of the STN limited our VISUAL-A approach based on individual T2-contrast in subject space, the core region of the n-map in MNI space widely surpassed the dorsal border of the atlas STN with about 30% located in the extranuclear compartment. Previous studies comparing the results of monopolar reviews and visual contact selection already reported higher levels of agreement for a visual approach compared to automatic sweet spot targeting, which might implicate a corrective impact of human interpretation during visual assessment [46,47]. We conclude that further development beyond the applied methodology is necessary to translate insights from probabilistic sweet spots to the individual patient.…”
Section: Discussionmentioning
confidence: 68%
“…Local voltage gradients are expected to be continuous and heterogeneous affecting neuron populations differently depending on myelinization and fiber orientation [48,49]. Correspondingly, Pavese et al reported frequent subsequent adjustments of amplitude suggestions based on VTA modeling, and Nordenström et al reported that clinical effect thresholds did not correlate well with predictions based on VTA modelling [46,47]. While probabilistic sweet spot mapping allows for the deduction of the desired position of the electric field, it does not provide sufficient information regarding the optimal extent of the electrical field, respectively, the necessary current in individual patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Imaging is also used to visualize the spread of electrical stimulation induced by DBS, such as the electric field (EF), to guide programming ( Hemm et al, 2005 ; Åström et al, 2009 ; Nguyen et al, 2019 ; Lange et al, 2021 ). When pooling individual patient data, one can create so-called clinical ‘sweet spots’, which are probabilistic stimulation maps predictive of good motor outcomes ( Dembek et al, 2019 ) and are already being used to guide programming ( Phibbs et al, 2014 ; Nordenström et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%